The Financial Impact of CSR Reporting on Emerging Market ‎Banks: An Empirical Investigation - Fatema, Mst. Rinu; Saha, Dr. Sumi; Banu, Dr. Mst. Hasna; Rahman, Md. Mahofuzur; Hossain, Dr. Md. Sumon (International Journal of Accounting and Economics Studies, 2025)
Banks play a vital role in sustaining a healthy economy, and corporate social responsibility ‎‎(CSR) initiatives provide them with legitimacy and a competitive advantage. This study ‎investigates the extent of CSR disclosure and its influence on the financial performance of ‎Bangladeshi banks. Secondary data were collected from the annual reports of ten listed ‎banks in Bangladesh over seven years (2017–2023) using a stratified random ‎sampling approach. The analysis employed content analysis, ANOVA, and panel regression ‎models, incorporating control variables such as firm age, firm size, independent directors, ‎leverage, and asset tangibility. Findings reveal that banks disclose, on average, 28.90% of ‎CSR-related information, while neglecting aspects such as product responsibility and minority ‎issues. Among the disclosed dimensions, contribution to the national exchequer ranks highest, ‎followed by education, community development, and disaster management. CSR disclosure ‎has shown a steady upward trend during the study period. Regression results demonstrate ‎that CSR reporting significantly and positively affects financial performance, suggesting that ‎greater CSR engagement is associated with higher profitability. Furthermore, leverage and ‎tangibility positively influence bank performance, while firm age, size, and independent ‎directors show no significant effect. Overall, the results highlight that robust CSR practices ‎not only boost banks’ profitability but also reinforce their legitimacy and competitiveness. ‎Policymakers should therefore promote standardized CSR reporting, and banks should ‎expand their disclosure to overlooked areas such as product responsibility and minority ‎inclusion to foster sustainable growth‎.